Pengaruh Corporate Governance Terhadap Financial Performance Dengan Earning Management Sebagai Variabel Intervening Pada Perusahaan Yang Terdaftar Di LQ45 - Angeline Feliciana Cythia; Devie Devie Devie (Business Accounting Review, 2017)
The purposes of this research is to analyze  the impact of corporate governance to financial performance with earnings management as intervening variable. The data analysis technique used was Partial Least Square (PLS)  with the calculation process assisted by SmartPLS software application program to process the data from Annual report. The results showed there were positive and significant influence of corporate governance towards financial performance, negative and siginificant of corporate governance towards earnings management and earnings management towards financial performance, and also there is no indirect influence of corporate governance towards financial performance through earnings management.